(untitled) (Physical Education, Health and Social Sciences, 2025)
This research aims at analyzing the impact of induction training program (ITP) on newly appointed teachers JESTs/PSTs in the domain of district Khairpur. As induction training is a process of equipping the basic skills, new strategies, instructional methods and pedagogies which are very closely relates to teaching learning process and also familiarize them to their profession as “Teaching is profession of prophets”. This research study analyze the impacts of ITP on the new teachers’ effectiveness on their job satisfaction and also improve their skills i.e. pedagogical or technological and improving their teaching practices by focusing on objectives like (1.) To investigate the impact of induction training programs on job satisfaction among newly appointed JESTs & PSTs in District Khairpur, Sindh. (2.) To assess the impact of induction training programs on teaching effectiveness among newly appointed JESTs & PSTs in District Khairpur, Sindh. (3.) To identify the strengths and weaknesses of the induction training programs for JESTs & PSTs in District Khairpur, Sindh. Mixed method (Quantitative and Qualitative method) were used in this study where survey questionnaire and conducting interviews were used as a tool for collecting data. A structured questionnaire was rolled out to 50 teachers at the selected talukas of district Khairpur and semi structured interviews were conducted with the teachers(CPs) and master trainers(MTs). The population of the research study Was the newly appointed teachers of district Khairpur who attended ITP ,50 teachers were selected as a sample by purposive sampling method to figure out sample size. A 5–point likert scale questionnaire was put into practice for the data collection. The entire data was analyzed through SPSS version 23. The statistical reliability score of Cronbach’s Alpha was 0.810, verifying the reliability results. The study search out some challenges faced by the trainee teachers and the trainers of ITP .Majority of the teachers were facing same issues and challenges like insufficient training materials, short time period given for the session for the specific tasks and for extensive amount of information and activities and a big challenge observed overall the training session was the use of ICT due to lack of resources .Meanwhile ,many of those approximately 50% trainee teachers were agreed from the overall quality of induction training and 56% trainee teachers were agreed that the topics which were covered in the training were relevant to their teaching needs. However, on ground situation of the schools and system of our schools is the basic hindrance for the newly appointed teachers for implementation of all these new strategies and time based need integration of ICT in teaching learning process but by the trial step of this group is a turning point for the change of system in schools by new trained teachers of district Khairpur. These results show that in spite of some challenges and some gaps the overall induction training program impacted positive on the newly appointed teachers’ effectiveness, job satisfaction, their teaching practices and so on